Analysis of Violations of the Cooperative Principles in the Film: Extraction 2 (2023) - Bagya aryanto; Adhan Kholis (J-Lalite: Journal of English Studies, 2023)
It would have been much better if both speakers and interlocutors could carry out conversations with each other that meet the rules of language when providing information in a communication that was carried out in real life, or it can be said that the communication carried out was communicative. Each response must be pertinent to the question, not wordy, and contain no lies or ambiguous conversations so that the speaker or interlocutor understands more about what was being discussed. As a result, cooperative principles in discourse are required. This study is connected to linguistic rules in the film Extraction II. This study aimed to (1) determine the type of violation of the cooperative maxims presented in the film Extraction II and (2) characterize the speakers’ motivation behind committing the violation. The methodologies and strategies employed in the Extraction II film research were the listening and note-taking methodology for data collection and then the researcher employed a data analysis technique, specifically the equivalent method, to identify the form of violation and motivation of the cooperative principle. In addition, the approach used in this study was qualitative. According to the findings of the research, there were seven violations of the cooperative principle in the film. These infractions included one violation of the maxim of quantity, three maxims of quality, two maxims of relevance, and one maxim of manner. In addition, the violation served six purposes: to convince, plan something, cover something, express annoyance, divert the topic of conversation, and confirm identity.